Signs Becoming Signs - Merrell, Floyd (Indiana University Press, 1991)
Signs Becoming Signs evinces a broad, transdisciplinary perspective based on the thinking of Charles Sanders Peirce. In an effort to account for our knowledge of a universe open to an infinity of interpretations, the author dissolves many of the age-old dichotomies of Western thought into complementarities, which are qualified by a pair of Peirce's key concepts, vagueness and generality.These two terms are placed within the contemporary context of the abstract disciplines (Zeno's paradoxes, the mathematical continuum, G. Spencer-Brown's laws of form, Godel's proof), physics (relativity, quantum theory, Susan Petrilli teaches in the Department of Foreign Languages and Literature at the Institute of the Philosophy of Language at the University of Bari. Bohm' s interconnectedness, Wheeler's participatory universe, Prigogine' s dissipative structures), biology (Maturana and Varel's autonomous living systems, Schrodinger's oneness of consciousness), and finally social psychology (Deleuze and Guattari's schizoanalysis).